Decision making autonomy and service delivery in local authorities: the case of Bulawayo city council. - Tshuma, Mzwanele W. (Midlands State University, 2019)
World over, municipalities or local authorities have been blamed for poor service delivery by both central government and local residents. Central government which has devolved power to local government accuses municipalities for poor service delivery, just as residents (tax payers) also point fingers at municipalities for the same reasons. It is with this project which aims to unveil some these constraints that affect service delivery, from the service providers angle of view. In addition it is with this research that aims to understand the term decision making autonomy, to understand if indeed the more the autonomy equals more quality and efficiency in service delivery. Upon understanding the factors that affect service delivery it can be noted that service delivery can be affected by various factors which may be divided into 2 categories which include external and internal causes. Decision making autonomy which is guaranteed by the constitution’s chapter 14 which illustrates on devolution of powers to local authorities so as to improve service delivery, increase participation and to empower the local communities. As the main idea in granting a certain level of autonomy is based on the notion that local people are best suited to address the locally arising problems, this dissertation will unravel and expose whether decision making autonomy has managed to serve its purpose, if not can it be done without?. As this research was both qualitative and quantitative some of the tools that were used include interviews and questionnaires so as to come up with the necessary data needed. Some of the findings that were drawn include that municipalities were set up to spearhead development and it is through the aspect of granting decision making autonomy that it can be realized, although this can improve services offered but it’s not guaranteed as there are several factors which influence service delivery. As part of the recommendations drawn some that were included are less to minimal interference from government should be observed so as to realize full potential of local authorities decision making autonomy granted to them through the constitution chapter 14, regarding service delivery there are some outdated policies which need to be revised such as the ministerial labour hiring freeze and laws that impedes on hiring essential stuff needed to improve services, hence being understaffed my affect negatively the quality of services offered.